부인암 여성의 성기능 구조모형 - 전나미; Chun, Na-Mi (Journal of Korean Academy of Nursing, 2008)
Purpose: This study was designed to construct and test a structural equation model on sexual function in women with gynecologic cancer. Methods: The model was constructed and tested under the hypotheses that women's physical changes in sexual function after gynecologic cancer treatment did not automatically lead to sexual dysfunctions. Women's psychosocial factors were considered to be mediating variables. Two hundred twelve women with cervical, ovarian, and endometrial cancer were recruited and asked to complete a survey on their physical factors, psychosocial factors and sexual function. Data was analyzed using SPSS WIN 12.0 and Amos WIN 5.0. Results: Predictors of sexual function in the final model were sexual attitude affected by physical distress and couple's age, sexual information affected by physical distress and couple's age, depression affected by physical distress, and marital intimacy affected by physical distress. Tumor stage and time since last treatment directly affected women's sexual function without any mediating psychosocial variables. However, body image did not affect women's sexual function. Conclusion: Nursing professionals should develop a tailored educational program integrating both physical and psychosocial aspects, and apply it to women and their spouses in order to promote sexual function in women with gynecologic cancer.